Visualization of particle physics concepts using virtual reality as a learning support tool for physics undergraduate - Jimmy Jupri; Dwi Sulisworo (Universitas Ahmad Dahlan, 2024)
This research aims to develop a Virtual Reality (VR) application to improve the understanding of particle physics concepts among undergraduate students. Following the waterfall development model, the application integrates a modern and interactive user interface and realistic 3D objects, developed using software such as Figma and Blender 3D. The research process included requirements analysis, user interface design, and implementation of additional features such as a video player and article viewer. These features are designed to enrich the learning experience and facilitate understanding of abstract particle physics concepts. Testing of the app showed that it functioned smoothly and effectively, offering an innovative and interactive learning method. This VR application is hoped to become a significant tool in physics education, helping students understand complex concepts better and increasing their engagement in the learning process.